Pengaruh Strategi Jigsaw Terhadap Kemampuan Komunikasi Siswa - Rahmawati, Adelia; Ningsih, Yulli Mulia; Azmi, Wildan; Yana, Nur Elyda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The ability to communicate with students in the teaching and learning process is very important for a teacher to pay attention to, with good communication, a good learning process is also established. The purpose of this study was to analyze the influence of the jigsaw method on students' communication skills. The research method used in this study was the experimental method, the population used in this study was class VA and VB, the methods used in analyzing the data the researcher carried out homogeneity tests, normality tests, distribution tests. The results of the study found that by using the jigsaw method in the learning process there was a significant influence on students' communication skills. Keywords: communication skills students,